2014
DOI: 10.4103/0019-5154.131389
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus: A clinical and immuno-histological analysis

Abstract: Background:Direct immunofluorescence examination is an important technique in the diagnosis of cutaneous inflammatory disorders including lichen planus, especially in clinically and histopathological doubtful cases.Objective:To study the diagnostic utility of intensity, number, and subtypes of positive immuno-reactants found in lichen planus.Materials and Methods:A detailed analysis of clinical as well as immuno-histological features of lichen planus cases was carried out.Results:The male to female ratio was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…2 LP is rare in children; however, the occurrence of LP in adults with 30–60 years old is relatively high. 3 As a chronic inflammatory disease, LP is considered to be related to infective, psychogenic, genetic, and autoimmune factors. 4 Although the exact etiology of LP remains unclear, current literature suggested that autoimmunity is pivotal in LP progression.…”
Section: Introductionmentioning
confidence: 99%
“…2 LP is rare in children; however, the occurrence of LP in adults with 30–60 years old is relatively high. 3 As a chronic inflammatory disease, LP is considered to be related to infective, psychogenic, genetic, and autoimmune factors. 4 Although the exact etiology of LP remains unclear, current literature suggested that autoimmunity is pivotal in LP progression.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for nail lichen planus is difficult, with a high rate of relapse, lack of cure for some irreversible features, and no definitive treatment guidelines or significant evidence-based studies. [11][12][13][14][15] High-potent topical corticosteroids were used in this case with occlusive for the nails.…”
Section: Case Presentationmentioning
confidence: 99%
“…Some patients may demonstrate other clinical subtypes of LP, like hypertrophic, bullous, pigmented, linear, annular, atrophic, hypertrophic, inverse, eruptive, ulcerative, or actinic LP, LP pemphigoides, and overlap syndromes [ 2 ]. Clinical presentation of the rarer subtypes of LP may be dissimilar to classic LP; however, histopathological examination reveals consistent features, including band-like subepidermal lymphocytic inflammatory infiltrate and degeneration of the basal cell layer of the epidermis [ 2 , 3 ]. Lichen planopilaris is considered as a follicular form of LP and classically presents as perifollicular erythema and scaling.…”
Section: Introductionmentioning
confidence: 99%